Determination of the pigment carotenoid astaxanthin content in the cells of the yeast strain Phaffia rhodozyma NT5 used as additive foods in aquaculture - Thuan, Tong Kim; Thuy, Tran Thanh (Academia Journal of Biology, 2014)
Astaxanthin is the main carotenoid pigment found in aquatic animals. salmonid, sea breams and shrimps cannot synthesize astaxanthin, therefore, dietary astaxanthin is the only source of body astaxanthin. The yeast P. rhodozyma is one of the new natural astaxanthin sources of biomass product of the Phaffia yeast is used as a color additive in aquaculture feeds to increase pink color of salmonid flesh. The culture conditions, the astaxanthin content of the yeast P. rhodozyma NT5 isolated from Vietnam and the influence of astaxanthin extracting methods were studied. The results showed that: 1. The growth of the yeast strain P. rhodozyma NT5 in shaked flasks under cultural conditions (concentration of sucrose 2%, pH = 5; temperature 220C ) reached its maximum value after 120 hours (11.42 g/l). The astaxanthin pigment formation began at 24 hours (33.32 mg/g) and the yield of the astaxanthin pigment reached its highest level (285.4 mg/g) after 120 hours. The cell mass were not significantly different from day 3 to day 5. 2. The mechanical method of the cell wall rupture with glass balls having a diameter of 2mm showed the best results. After 30 minutes, 92% of yeast cells were ruptured compared with 75% ones by glass powders. The rupture of the fresh cell walls gave better result (100% compared with 92% of dry cells). 3. The extract of the pigment astaxanthin from fresh yeast mass with acetone + petroleum ether (PE) gave the highest effect; the astaxanthin content reached 327 mg/g dry mater. At the time, astaxanthin content extracted with acetone or ethanol reached only 296.4 mg/g and 118.96 mg/g, respectively.